KAJIAN NARATIF ANTROPOLOGI DAN PENDIDIKAN - S, Laurensius Arliman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Anthropology of science education that was born in the mid-20th century. The question that arose at that time was the extent to which education could change society, the frame of mind at that time how to develop development in developing countries and indeed at that time developed countries like Europe were thinking of doing it. changes in society develop through its programs, so that educational anthropology tries to find patterns of community learning culture that can create a change.